Agricultural Transformation and its Contribution to Economic Development in South Asian and African Countries - (:unkn) unknown (My University, 2025)
Agricultural transformation is central to economic development, driving modernization, productivity enhancement, and integration into broader economic systems. This study compares South Asia and Africa, analyzing their distinct trajectories influenced by sustainable practices, policy reforms, and technological advancements. In South Asia, agricultural employment declined sharply, with Bangladesh dropping from 80% in 1973 to 35% in 2023, and India from 70% to 37%. Africa saw a more gradual decline, from 70% to 48% during the same period. Productivity improvements highlight regional progress, with agricultural productivity growth rising in Bangladesh (3.3% to 4.1% by 2023) and Kenya (3.3% to 4.1%), while manufacturing productivity surged in Kenya (6.6%) and India (5.2%). South Asia's growth leverages high-yield crops and market integration from the Green Revolution, while Africa focuses on climate-smart agriculture, diversification, and community-based solutions to address climate vulnerabilities and infrastructure gaps. Both regions emphasize sustainability as a resilience strategy. Using a four-stage paradigm of agricultural transformation, the study underscores the significance of transitioning from subsistence to high-value, technology-driven agriculture for economic diversification and resilience. By analyzing labor productivity, GDP per capita, and crop production indices, the research demonstrates agriculture's critical role in fostering sustainable development and economic growth across both regions.
Keywords: African Research